Tell me who you are [large type] - Luna, Louisa (Thorndike Press large print high octane., 2024)
"Brooklyn psychiatrist Dr. Caroline Strange is certain she knows what's best for her patients, her family, and pretty much everyone else, but that all changes when a troubled young man arrives for his appointment and makes a pair of alarming confessions: I am going to kill someone, and I know who you really are. Dr. Caroline is accustomed to hearing her patients' deepest, darkest secrets, but it seems Nelson Schack may be one step ahead when detectives show up later that day, inquiring about a missing woman. It looks like Nelson has made good on his threat--yet somehow it's Dr. Caroline who becomes the prime suspect. Convinced the police are incompetent, Dr. Caroline takes matters into her own hands, chasing down the elusive Nelson and running headlong into a past she has spent her entire life trying to forget. As she closes in on her target, all the polished pieces of her manicured life splinter when people begin to question who she really is. Harrowing, unpredictable, and compulsively readable, the award-winning author Louisa Luna's Tell Me Who You Are is an utterly gripping psychological thriller that begs the question: Can a person ever really outrun their past?"--